The impact of diabetes on the relationship of coronary artery disease and outcome: a study using multimodality imaging - Mäenpää Matias; Kujala Iida; Harjulahti Esa; Stenström Iida; Nammas Wail; Knuuti Juhani; Saraste Antti; Maaniitty Teemu (BMC, 2025)
Background
Patients with prediabetes or diabetes are at increased risk of developing cardiovascular disease and adverse outcomes. First-line coronary computed tomography angiography (CTA) followed by selective use of positron emission tomography (PET) myocardial perfusion imaging is a feasible strategy to diagnose and risk-stratify patients with suspected coronary artery disease (CAD). The aim of the present study was to study whether diabetes changes the relationship of CAD and long-term outcome.
Methods
We retrospectively identified consecutive symptomatic patients who underwent coronary CTA for suspected CAD. In patients with suspected obstructive CAD on CTA, myocardial ischemia was evaluated by 15O-water PET myocardial perfusion imaging. The relationship of the phenotype of CAD and long-term outcome in patients with no diabetes, prediabetes, or type 2 diabetes was investigated. A composite endpoint included all-cause mortality, myocardial infarction (MI), and unstable angina pectoris (UAP).
Results
A total of 1743 patients were included: 1214 (70%) non-diabetic, 259 (15%) prediabetic, and 270 (16%) type 2 diabetic patients. During 6.43 years of median follow-up, 164 adverse events occurred (106 deaths, 41 MIs, 17 UAPs). The prevalence of normal coronary arteries on CTA was highest in the non-diabetic patients (39%). The prevalence of hemodynamically significant CAD (abnormal perfusion) increased from 14% in non-diabetic patients to 20% in prediabetic and 27% in diabetic patients. The event rate was lowest in patients with normal coronary arteries and highest in patients with concomitant type 2 diabetes and hemodynamically significant CAD (annual event rate 0.2% vs. 4.7%). However, neither prediabetes nor diabetes were independent predictors of the composite adverse outcome after adjustment for the clinical risk factors and imaging findings.
Conclusions
Coronary CTA followed by selective downstream use of PET myocardial perfusion imaging predicts long-term outcome similarly in non-diabetic and diabetic patients.